A Framework for User Centric LCA Tool Development for Early Planning Stages of Buildings - Hollberg, Alexander; Tjäder, Maria; Ingelhag, Gerda; Wallbaum, Holger (Frontiers in Built Environment, 2022)
As the high greenhouse gas (GHG) emissions caused by the construction and real estate sector receive more attention, more and more countries include an environmental assessment of buildings based on Life Cycle Assessment (LCA) in their building regulations. Sweden will introduce mandatory climate declarations in January 2022, for example. To support stakeholders in conducting the climate declarations and using the results to reduce GHG emissions, user-friendly tools for early planning stages are needed. The aim of this study is to develop a framework for user centric development of such tools. The framework builds on three steps; 1) interviewing stakeholders to define tool requirements, 2) developing a prototype tool according to the requirements, and 3) evaluating it based on user feedback. We developed and tested the framework in the Swedish context with the aim to provide a blueprint applicable in other countries and contexts. The primary target users are architects but also engineers and real estate developers working in early phases. The results show that the users’ expectations can be met when the requirements are integrated from the very beginning. In the current version, the developed building LCA tool only targets the embodied GHG emissions from the production and construction phase of the building, but it could be extended to include further life cycle phases in the future.